2011
DOI: 10.1007/s10096-011-1478-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-adherence to antimicrobial treatment guidelines results in more broad-spectrum but not more appropriate therapy

Abstract: Mortality in patients admitted with sepsis is high and the increasing incidence of infections with multiresistant bacteria is a worldwide problem. Many hospitals have local antimicrobial guidelines to assure effective treatment and limit the use of broad-spectrum antibiotics, thereby reducing the selection of resistant bacteria. We evaluated adherence to the antimicrobial treatment guidelines of our hospital in patients presenting to the emergency department (ED) with sepsis and assessed the in vitro susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
0
16
0
3
Order By: Relevance
“…To include more resistant but often less prevalent pathogens, the empirical therapy of a severe infection is usually broad-spectrum. 5,10 The downside of this strategy is that the prescribed antibiotics are often more broad-spectrum than necessary 11 or even are used in the absence of a bacterial infection. 12,13 This may have potentially deleterious consequences such as anaphylactic reactions, antibiotic resistance, and high costs.…”
Section: Introductionmentioning
confidence: 99%
“…To include more resistant but often less prevalent pathogens, the empirical therapy of a severe infection is usually broad-spectrum. 5,10 The downside of this strategy is that the prescribed antibiotics are often more broad-spectrum than necessary 11 or even are used in the absence of a bacterial infection. 12,13 This may have potentially deleterious consequences such as anaphylactic reactions, antibiotic resistance, and high costs.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are previous studies that have shown that infections are commonly diagnosed with limited clinical criteria and often treated without lab confirmation [4]. Beyond this, antibiotic treatment is often continued after negative lab results are received [5].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In sepsis patients, non-adherence to guidelines can result in more broadspectrum treatment but not more appropriate treatment. 11 In other settings it has been shown that including physicians in the development of local guidelines and thereby giving them responsibility and ownership, facilitates adherence to local guidelines. 12 Other strategies are the combination of intense education, feedback, and evaluation, or the introduction of a simple monitoring form that increases the focus on prescription and the use of antimicrobial treatment.…”
Section: Discussionmentioning
confidence: 99%